2019
DOI: 10.3238/arztebl.2019.0083
|View full text |Cite
|
Sign up to set email alerts
|

Pain on the Plantar Surface of the Foot

Abstract: ain on the plantar surface of the foot subsumes constellations of symptoms arising from various underlying conditions. In this article we present the clinical findings of the diseases that most commonly cause plantar pain, the diagnostic procedures available, and an overview of the treatment options. For reasons of space we restrict ourselves to the two most highly prevalent conditions, plantar fasciitis and metatarsalgia. Methods We carried out a selective survey of the literature in the PubMed database. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 70 publications
0
30
0
7
Order By: Relevance
“…All the above studies demonstrate that the MG experiences greater mechanical loading during daily activities. Clinically, most studies have reported that reduced muscle stiffness can alleviate the symptoms of patients with PF 2,6,9,21 . For example, chronic symptoms lasting longer than 4 months might cause the tissue to be stiffer and to become more difficult to stretch 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the above studies demonstrate that the MG experiences greater mechanical loading during daily activities. Clinically, most studies have reported that reduced muscle stiffness can alleviate the symptoms of patients with PF 2,6,9,21 . For example, chronic symptoms lasting longer than 4 months might cause the tissue to be stiffer and to become more difficult to stretch 2 .…”
Section: Discussionmentioning
confidence: 99%
“…They were recruited from Luoyang Orthopaedic Hospital of Henan Province. The inclusion criteria for the patients with PF were as follows 6,16 : 1. heel pain at the medial plantar, 2. intensity of pain upon being provoked ≥3/10 on a visual analogue scale (VAS), 3. worsening pain when waking up or after a period of rest, 4. pain duration longer than 6 months, 5. not having neuromuscular disease, tendon rupture, musculoskeletal injury of the lower limb or anomaly on ultrasound. Patients who had received any treatment of the ankle or foot, such as steroid injection, shock wave therapy and surgery, were excluded from the study 11,16 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over a decade after its first description, several therapeutic modalities have been used for the management of painful heel spur and plantar fasciitis. Modification of life style to prioritize resting, losing weight and avoiding from intensive physical workload, analgesics, cold compresses, iontophoresis, antiinflammatory agent and steroid injections, stretching exercises and physical therapy, laser, microwave, ultrasound therapy, orthotics and shoe modifications, foot orthoses and insoles, heel pads, efforts to decrease pressure on the affected site, orthopedic interventions, and radiation therapy (RT) are among the methods for eradicating or alleviating pain from heel spur and plantar fasciitis (8)(9)(10). The use of foot orthoses and insoles may result in functional improvement and reduction of pain from plantar fasciitis and heel spurs (9,10).…”
Section: Original Articlementioning
confidence: 99%